Morphological Characterization of Yam Genotypes from Different Geographic Origins in Angola (Global Journal of Science Frontier Research, 2025)
Yam (Dioscorea spp.) is a vegetable of great economic and social importance, cultivated in tropical and subtropical regions. It is a staple food for millions of people, especially in West Africa, valued for its tuberous roots rich in carbohydrates, proteins, vitamins and minerals. In addition to its nutritional value, yam has cultural and medicinal significance, used in ceremonies and therapies. In Angola, climatic and geographic diversity favors the cultivation of different yam genotypes, resulting in a genetic heritage that is crucial for crop resilience and food security. The morphological characterization of genotypes allows the identification of varieties with desirable attributes, such as disease resistance, productivity and nutritional quality, facilitating genetic improvement programs. This study aims to morphologically characterize yam genotypes from different geographic origins in Angola, contributing to the knowledge and conservation of genetic diversity and the development of sustainable agricultural strategies.
Keywords: dioscorea spp; genetical diversity; descriptor analysis